2002
DOI: 10.1002/pros.10063
|View full text |Cite
|
Sign up to set email alerts
|

Elevated serum progastrin‐releasing peptide (31–98) in metastatic and androgen‐independent prostate cancer patients*

Abstract: The clinical results demonstrated the existence of a regulatory mechanism for GRP, which to date had only been observed in cell lines. These findings suggest that GRP is a growth factor potentially upregulated by androgen but that does not rely principally on androgen modulation. The large overlap in levels of ProGRP among the groups limits the use of this value as a monitoring tool. Measurement of ProGRP, however, does have potential as an independent parameter to evaluate androgen-independent progression and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
0

Year Published

2002
2002
2022
2022

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 42 publications
(24 citation statements)
references
References 36 publications
(36 reference statements)
1
23
0
Order By: Relevance
“…Levels of PSA are highly upregulated during prostate cancer progression (49). Pezzato et al report some new activities of PSA which include degradation of gelatin, degradation of type IV collagen in reconstituted basement membrane (Matrigel) and activation of progelatinase A (MMP-2), but not pro-MMP-9, in a cell-free system (50).…”
Section: Green Tea Polyphenols and Prostate Cancermentioning
confidence: 99%
“…Levels of PSA are highly upregulated during prostate cancer progression (49). Pezzato et al report some new activities of PSA which include degradation of gelatin, degradation of type IV collagen in reconstituted basement membrane (Matrigel) and activation of progelatinase A (MMP-2), but not pro-MMP-9, in a cell-free system (50).…”
Section: Green Tea Polyphenols and Prostate Cancermentioning
confidence: 99%
“…Moreover, the serum CGRP levels of the hormone-resistant patients were significantly higher than those of the hormone-sensitive patients. Similar to other NE markers such as ProGRP, in stage D3 patients higher serum levels were observed than in stage D1 or D2 patients, and the measurement of the serum level is a potential parameter that affects androgen-independent progression [7,8] . Moreover, the serum CgA, NSE, and ProGRP reportedly have some significant prognostic information with or without measurement of PSA level [3][4][5]8] .…”
Section: Discussionmentioning
confidence: 71%
“…Prostate-specific antigen (PSA) is a very well-known tumor marker in the diagnosis of PCa [13] , and it reportedly correlates with the serum NE markers including CgA and ProGRP in the untreated PCa patients, but not in the PCa patients treated with HT [4,7] . Although we also analyzed the correlation between PSA and the serum CGRP level in the untreated PCa patients, no significant correlation was detected in our previous study [12] .…”
Section: Discussionmentioning
confidence: 99%
“…Several previous reports demonstrated that NE differentiation evaluated by CgA expression in the untreated prostate cancer specimens obtained by radical prostatectomy was not associated with the tumor stage and Gleason grade 1,3 . Among the circulating NE markers, CgA, NSE, and ProGRP were significantly associated with the clinical stage, but not with the histological grade probably due to the tumor volume dependency 7,8 , 10 . Although the number of patients entered in this study was small, the present study showed that the serum CGRP level was significantly associated with not only the tumor stage but also the histological grade, suggesting that CGRP may become potentially a new NE marker which reflects the tumor volume or aggressiveness.…”
Section: Discussionmentioning
confidence: 96%